Lung function and indicators of exposure to indoor and outdoor particulate matter among asthma and COPD patients. Issue 1 (6th September 2009) - de Hartog, J J; Ayres, J G; Karakatsani, A; Analitis, A; Brink, H ten; Hameri, K; Harrison, R; Katsouyanni, K; Kotronarou, A; Kavouras, I; Meddings, C; Pekkanen, J; et al.
Abstract : Objectives: Misclassification of exposure related to the use of central sites may be larger for ultrafine particles than for particulate matter ⩽2.5 μm and ⩽10 μm (PM2.5 and PM10 ) and may result in underestimation of health effects. This paper describes the relative strength of the association between outdoor and indoor exposure to ultrafine particles, PM2.5 and PM10 and lung function. Methods: In four European cities (Helsinki, Athens, Amsterdam and Birmingham), lung function (forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1 ) and peak expiratory flow (PEF)) was measured three times a day for 1 week in 135 patients with asthma or chronic obstructive pulmonary disease (COPD), covering study periods of >1 year. Daily concentrations of particle number, PM2.5 and PM10 were measured at a central site in each city and both inside and outside the subjects' homes. Results: Daily average particle number concentrations ranged between 2100 and 66 100 particles/cm 3 . We found no association between 24 h average particle number or particle mass concentrations and FVC, FEV1 and PEF. Substituting home outdoor or home indoor concentrations of particulate air pollution instead of the central site measurements did not change the observed associations. Analyses restricted to asthmatics also showed no associations. Conclusions: No consistent associations between lung function and 24 h average particle number or particle mass concentrations were found in panels of patients with mild to moderate COPD or asthma. More detailed exposure assessment did not change the observed associations. The lack of association could be due to the high prevalence of medication use, limited ability to assess lagged effects over several days or absence of an effect.